2008
DOI: 10.1111/j.1462-5822.2008.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial infection-mediated mucosal signalling induces local renal ischaemia as a defence against sepsis

Abstract: SummaryAscending urinary tract infections can cause extensive damage to kidney structure and function. We have used a number of advanced techniques including multiphoton microscopy to investigate the crucial early phases of uropathogenic Escherichia coli induced pyelonephritis within a living animal. Our results reveal a previously undescribed innate vascular response to mucosal infection, allowing isolation and eradication of the pathogen. The extremely rapid host response to mucosal infection was highlighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 105 publications
(156 citation statements)
references
References 36 publications
7
146
0
3
Order By: Relevance
“…The same E. coli strain, missing only one virulence factor, required a far greater time to initiate this protective process. Tissue concentrations of cytokines were markedly elevated in the affected area, but were undetectable adjacent to the injected areas (66). Finally, prevention of this microvascular response resulted in widespread organ dissemination of the injected E. coli and death of the rat within 24 hours, which was not observed with the intact system (66).…”
Section: Proximal Tubule Cellsmentioning
confidence: 89%
See 1 more Smart Citation
“…The same E. coli strain, missing only one virulence factor, required a far greater time to initiate this protective process. Tissue concentrations of cytokines were markedly elevated in the affected area, but were undetectable adjacent to the injected areas (66). Finally, prevention of this microvascular response resulted in widespread organ dissemination of the injected E. coli and death of the rat within 24 hours, which was not observed with the intact system (66).…”
Section: Proximal Tubule Cellsmentioning
confidence: 89%
“…A series of elegant studies directly demonstrated this phenomenon using fluorescent cytopathologic E. coli that were microinjected into early PT segments, with cellular and physiologic responses recorded using two-photon microscopy (64)(65)(66). Attachment to the apical membrane, but without penetration into or through the PTC monolayer barrier, resulted in rapid and selective termination of blood flow to the adjacent area, leading to vascular isolation of the infected area with localized hypoxia, wbc migration/infiltration, and necrosis.…”
Section: Proximal Tubule Cellsmentioning
confidence: 99%
“…60 Albumin uptake by nonselective fluidphase endocytosis is probably a quantitatively important process in PTCs, as shown by the rapid cellular uptake of molecules not having receptors on the apical membrane, such as neutral fluorescent dextrans (markers of fluid-phase endocytosis). 61,62 The endocytic apparatus is found throughout the PT, although clathrincoated pits and vesicles are notably fewer in the S3 segment. 63 Expectedly, protein reabsorption and degradation are greatest in the S1 segment of the PTCs and least in the S3 segment.…”
Section: Endocytosis By the Ptmentioning
confidence: 99%
“…This reasoning is supported by observations derived from models of singlenephron tubular obstruction 48 and localized microinjection of Escherichia coli into early proximal tubule lumens. [49][50][51] Therefore, there seems to be a bidirectional and possibly synergistic crosstalk within the complex tubule-capillary microenvironment, with the sequence of events depending on the nature of insult. 23 Although microcirculatory changes may lead to tubular injury, the reverse may also be true.…”
Section: Peritubular Microcirculation In Akimentioning
confidence: 99%